Long QT syndrome in a child of 1,5 years old: clinical case - A. N. Roshchupkin; G. Yu. Evstifeeva; E. I. Danilova; Z. A. Veterkova; N. V. Loginova; N. N. Usenkova; A. I. Shishkina (Лечащий Врач, 2025)
Background. QT interval is an electrocardiographic index reflecting the processes of depolarization and repolarization of the ventricular myocardium, the electrophysiological basis of which is the state of ion channels of the cardiomyocyte membrane. Long QT syndrome (LQTS) is a life-threatening heart rhythm disorder and one of the reasons of a sudden cardiac death. Meanwhile, this term combines a diverse and extensive group of diseases which cause a deceleration of the repolarization phase of ventricular myocardium due to the pathology of ion channels of the cardiomyocyte membrane. The basis of the diagnosis of this condition is the ability of a doctor of any specialty to interpret the results of electrocardiography correctly before the occurrence of the first clinical manifestations.Objective. The aim of the publication of this clinical case was the necessity to acquaint pediatric physicians with atypical manifestations of LQTS in a child and features of diagnostic screening and therapeutic measures. To enhance knowledge of the medical community and to raise awareness of patients will allow to reduce the number of some life-threatening conditions in children with LQTS.Materials and methods. A 1,5-year-old child with a prenatally identified bradycardia and a dual chamber frequency-adapted pacemaker implanted on the third day of life. The detailed anamnesis of the child`s life, the results of a clinical, instrumental and genetic examinations and the peculiarities of the selection of the antiarrhythmic therapy are presented.Conclusion. The peculiarities of the clinical case of LQТS (early manifestation of the disease, lack of genetic anamnesis, an atypical clinical picture with the accession of bradycardia due to an extremely long QT interval and conditions of manifestations of syncopal states, lack of a positive effect on the specific antiarrythmic therapy) testify to the polymorphism of the described syndrome. All of the above testifies to the necessity of a more profound study of the correlation of the clinical manifestations with the results of a genetic testing.